The Implementation of Public Sector Accounting, Internal Control, and Transparency on the Performance of Government Institutions: Evidence from the Jakarta Provincial Government - Siti Syifani Kusuma Ayu Syifanika; Adam Zakaria; Muhammad Yusuf (PT. BATARI EDU CALYA, 2025)
This study aims to examine the influence of public sector accounting, internal control, and transparency on the performance of financial reporting within the Jakarta Provincial Government. The population of this research consists of employees of the Jakarta Provincial Inspectorate. A total of 45 respondents were selected as the research sample using a questionnaire distribution method. The collected data were processed using SPSS software and analyzed through multiple linear regression techniques. The findings indicate that competency in human resources, accountability, and supervision have a positive and significant effect on the performance quality of financial reports within the Jakarta Provincial Government.